The Role of Modern Observation in Understanding the Beginning of the Hijri Month - Frangky Suleman; Djamila Usup (IAIN Manado, 2021)
This study aims to observe the determination of the beginning of the Hijri month in the implementation of Islamic holidays and contribute to modern society. The implementation of this research uses phenomenological methods and scientific approach methods, where both methods will combine several conjunction theories that occur with the results of observations. The Ministry of Religion of the Republic of Indonesia made observations with several criteria used from observations in 1970 with the height of the new moon 2°, the elongation distance between the moon and the sun reaching 3° is the distance between the moon and the sun. The age of the sun and moon when it reaches 8 hours from ijtima. The results found are that for now, with light pollution, the new moon, an object, cannot reach a height of < 2° because the parameter in determining the image of the crescent moon is the object in the form of a thin and dim line. It is concluded that the observation of the new moon with a height of < 2° could not observe, either by using tools or with the naked eye. So science is the solution to understand the theory and implementation of determining the beginning of the Hijri month.